2002
DOI: 10.1017/s1352465802001078
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Symptoms of Ocd and Appraisal of Responsibility During Cognitive Behavioural Treatment: A Pilot Study

Abstract: A consecutive series of six adolescents referred for obsessive compulsive disorder were treated using a cognitive behavioural approach that included procedures intended to:(1) reach a shared understanding of the psychological nature of the problem; (ii) normalize intrusive thoughts; (iii) help the patient to reappraise notions of responsibility; and (iv) help the patient re-evaluate the basis of their fears. The effects of treatment were measured using standardized questionnaires designed to elicit beliefs abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…Williams et al (2002) and Storchheim and O'Mahony (2006) assumed that changes in beliefs and compulsive behaviour would occur in tandem, and results were in line with this hypothesis. Rhéaume and Ladouceur (2000) also investigated possible differences between ERP and CT in processes of change, and found that in both treatments, cognitive changes sometimes preceded behavioural change, and, in some instances, followed behavioural change within the same subject.…”
Section: Process Studies In Ocdsupporting
confidence: 61%
See 1 more Smart Citation
“…Williams et al (2002) and Storchheim and O'Mahony (2006) assumed that changes in beliefs and compulsive behaviour would occur in tandem, and results were in line with this hypothesis. Rhéaume and Ladouceur (2000) also investigated possible differences between ERP and CT in processes of change, and found that in both treatments, cognitive changes sometimes preceded behavioural change, and, in some instances, followed behavioural change within the same subject.…”
Section: Process Studies In Ocdsupporting
confidence: 61%
“…The studies of Rhéaume and Ladouceur (2000), Storchheim and O'Mahony (2006) and Williams et al (2002) explicitly investigated changes in beliefs both during C(B)T and ERP, based on the cognitive model of OCD. All three studies reported decreases in dysfunctional beliefs during successful treatment, irrespective of type of treatment, which is in line with the conclusions based on treatment outcome studies that successful treatment of OCD is related to signifi cant changes in obsessional beliefs (Bouvard, 2002;Emmelkamp et al, 2002).…”
Section: Process Studies In Ocdmentioning
confidence: 99%
“…Although a failure to find changes in depression symptoms is not unusual in trials of CBT for OCD [25], we had predicted a change in OCD symptoms paralleling responsibility cognitions as was found in a pilot study [36]. One possibility is that as found by Anholt et al [3] the changes in behaviour rather than the changes in cognitions were the most significant feature of treatment.…”
Section: Discussionmentioning
confidence: 53%
“…The therapists did not insist on waiting until the uncomfortable feelings had subsided as is required by exposure and response prevention. A pilot study [36] of this form of CBT with young people suggested that the changes in symptoms were paralleled by the changes in the responsibility beliefs which initiate and maintain compulsive behaviours. The techniques also affect meta-cognition in that they alter the beliefs about the nature and meaning of cognitions associated with OCD.…”
Section: Introductionmentioning
confidence: 99%
“…Los tratamientos aplicados son, en la mayoría de los casos, programas multicomponente, compuestos, al igual que en los estudios de caso y caso único, por EPR y técnicas cognitivas, en los cuales la familia es implicada en mayor o menor nivel según el protocolo seguido o la edad de los sujetos. Sin embargo, también encontramos evaluaciones de programas esencialmente conductuales, compuestos sólo por EPR (Apter et al, 1984;Bolton et al, 1983, Scahill et al, 1996 y programas puramente cognitivos (Williams et al, 2002). Los protocolos o manuales, seguidos en la aplicación de las intervenciones son los de March y Mulle (1998), Lewin et al (2005), Barrett (2009), Piacentini et al (1998), Schwartz (1996, Wells (1997) y Salkovskis (1998).…”
Section: Discussionunclassified